Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infections and Reinfections Among Fully Vaccinated and Unvaccinated University Athletes—15 States, January–November 2021 . (30th June 2022) - Good, Mary K; Czarnik, Michaila; Harmon, Kimberly G; Aukerman, Doug; O'Neal, Catherine S; Day, Carly; Goerl, Kyle; Sifre, Katlynn; Fink, Steven; Riggs, Margaret A
Abstract: Background: Limited data currently exist on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among fully vaccinated persons or reinfections in college-aged populations. Centers for Disease Control and Prevention (CDC) partnered with National Collegiate Athletic Association (NCAA) institutions to analyze retrospective data and present characteristics of positive coronavirus disease 2019 (COVID-19) cases among student athletes 18 years of age and older. Methods: De-identified, individual-level data contributed by 21 universities on 1378 student athletes who tested positive for SARS-CoV-2 from January through November 2021 (pre-Omicron) were examined to determine percentages of infection among unvaccinated, partially vaccinated, and fully vaccinated individuals (breakthrough infections) as well as reinfections. Comparisons by demographic characteristics and regions were also made to further characterize these infections. Results: Among the 1378 student athletes positive for SARS-CoV-2, 1070 (77.6%) were infected when unvaccinated and 22.4% (n = 308) were infected after full vaccination. There was a significant difference between Black (14.7%, n = 40) and White (23.9%, n = 168) student athletes who experienced a SARS-CoV-2 infection after being fully vaccinated ( P  < .01). Proportions of infections among fully vaccinated individuals did not differ statistically by sex ( p  = 0.06). Conclusions: This article adds to the knowledge of SARS-CoV-2 infections among fully vaccinated individuals in college-aged populations. The level of infections among fully vaccinated student athletes indicates the need for maintaining precautions to prevent infection. Further study of COVID-19 vaccination, infection, and reinfection among the well-resourced and diverse population of student athletes might contribute further understanding of factors that play a role in health equity among young adults. Abstract : This article adds to the knowledge of coronavirus disease 2019 (COVID-19) infections among fully vaccinated individuals in college-aged populations. The level of infections among fully vaccinated student athletes indicates the need for maintaining precautions to prevent infection.